Actin-resistant DNAse I Expression From Oncolytic Adenovirus Enadenotucirev Enhances Its Intratumoral Spread and Reduces Tumor Growth - Tedcastle, A; Illingworth, S; Brown, A; Seymour, L; Fisher, K (Elsevier, 2016)
Spread of oncolytic viruses through tumor tissue is essential to effective virotherapy. Interstitial matrix is thought to be a significant barrier to virus particle convection between "islands" of tumor cells. One way to address this is to encode matrix-degrading enzymes within oncolytic viruses, for secretion from infected cells. To test the hypothesis that extracellular DNA provides an important barrier, we assessed the ability of DNase to promote virus spread. Nonreplicating Ad5 vectors expressing actin-resistant DNase (aDNAse I), proteinase K (PK), hyaluronidase (rhPH20), and chondroitinase ABC (CABC) were injected into established DLD human colorectal adenocarcinoma xenografts, transcomplemented with a replicating Ad5 virus. Each enzyme improved oncolysis by the replicating adenovirus, with no evidence of tumor cells being shed into the bloodstream. aDNAse I and rhPH20 hyaluronidase were then cloned into conditionally-replicating group B adenovirus, Enadenotucirev (EnAd). EnAd encoding each enzyme showed significantly better antitumor efficacy than the parental virus, with the aDNAse I-expressing virus showing improved spread. Both DNase and hyaluronidase activity was still measurable 32 days postinfection. This is the first time that extracellular DNA has been implicated as a barrier for interstitial virus spread, and suggests that oncolytic viruses expressing aDNAse I may be promising candidates for clinical translation.